2014
DOI: 10.1007/s00228-014-1756-0
|View full text |Cite
|
Sign up to set email alerts
|

Reported ingested dose of paracetamol as a predictor of risk following paracetamol overdose

Abstract: There is a positive correlation between reported ingested dose of paracetamol and subsequent chance of a PPC being above a defined treatment line; however, ingested dose of paracetamol alone is a poor risk assessment tool in accurately determining need for treatment with an antidote.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Despite the overwhelming number of publications from Western countries which recommend the use of acetaminophen concentrations as the gold standard for determining the risk of hepatotoxicity in an acute overdose, such a tool remains elusive for the majority of clinicians who practice toxicology in resource‐limited settings such as Thailand and around the world 9,17 . And while it is true that dose‐estimation is seen as a sub‐optimal method for determining the initiation of NAC therapy, it continues to be a requisite in these parts of the world 9,10 . An informal survey among 83 physicians from 63 hospitals in Thailand who utilize the Siriraj Hospital Poison Information and Clinical Toxicology Service reveals that only 22 hospitals possess the capability to perform acetaminophen level assay and the turnaround times range from within 4 h (4 hospitals) to 24 h (10 hospitals) and beyond 24 h (8 hospitals).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the overwhelming number of publications from Western countries which recommend the use of acetaminophen concentrations as the gold standard for determining the risk of hepatotoxicity in an acute overdose, such a tool remains elusive for the majority of clinicians who practice toxicology in resource‐limited settings such as Thailand and around the world 9,17 . And while it is true that dose‐estimation is seen as a sub‐optimal method for determining the initiation of NAC therapy, it continues to be a requisite in these parts of the world 9,10 . An informal survey among 83 physicians from 63 hospitals in Thailand who utilize the Siriraj Hospital Poison Information and Clinical Toxicology Service reveals that only 22 hospitals possess the capability to perform acetaminophen level assay and the turnaround times range from within 4 h (4 hospitals) to 24 h (10 hospitals) and beyond 24 h (8 hospitals).…”
Section: Discussionmentioning
confidence: 99%
“…Optimization of an appropriate dose-estimate threshold means initiating treatment in patients with reasonable risks for hepatotoxicity and minimizing the costs incurred by overtreatment with the antidote. [7][8][9][10] These diverse sets of data echo the reality that, despite its long-regarded use in toxicology, there is lacking evidence of sensitivity and specificity of the 150 mg/kg dose-estimate at predicting hepatotoxicity when using the 150 mg/L treatment line. And most importantly, there can be 2.5%-10.5% of patients who are undertreated and 39.4%-95% overtreated depending on which dose-estimate criteria are being applied.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Recent studies noted that, while there is an overall correlation between reported dose and serum concentration, some patients reported ingesting doses that were not consistent with the measured concentrations based the standard pharmacokinetic parameters for paracetamol. Moreover, a retrospective study of over 1200 paracetamol overdose patients concluded that self‐reported dose alone was a poor assessment tool in determining the need for overdose treatment. In summary, knowledge of the ingested paracetamol dose following self‐harm poisoning could help inform treatment plans, aid in validating the history in reports of toxicity, and identify patients who have overdosed, but have provided inaccurate dosing histories.…”
Section: Introductionmentioning
confidence: 99%